Detection of TurboID fusion proteins by fluorescent streptavidin outcompetes antibody signals and visualises targets not accessible to antibodies - Odenwald, Johanna; Gabiatti, Bernardo; Braune, Silke; Shen, Siqi; Zoltner, Martin; Kramer, Susanne (eLife, 2024)
Immunofluorescence localises proteins via fluorophore-labelled antibodies. However, some proteins evade detection due to antibody-accessibility issues or because they are naturally low abundant or antigen density is reduced by the imaging method. Here, we show that the fusion of the target protein to the biotin ligase TurboID and subsequent detection of biotinylation by fluorescent streptavidin offers an 'all in one' solution to these restrictions. For all proteins tested, the streptavidin signal was significantly stronger than an antibody signal, markedly improving the sensitivity of expansion microscopy and correlative light and electron microscopy. Importantly, proteins within phase-separated regions, such as the central channel of the nuclear pores, the nucleolus, or RNA granules, were readily detected with streptavidin, while most antibodies failed. When TurboID is used in tandem with an HA epitope tag, co-probing with streptavidin and anti-HA can map antibody-accessibility and we created such a map for the trypanosome nuclear pore. Lastly, we show that streptavidin imaging resolves dynamic, temporally, and spatially distinct sub-complexes and, in specific cases, reveals a history of dynamic protein interaction. In conclusion, streptavidin imaging has major advantages for the detection of lowly abundant or inaccessible proteins and in addition, provides information on protein interactions and biophysical environment.
Keywords: biotinylace; nuclear pore; Humans; BioID; Antibodies; Trypanosoma brucei; human; Protozoan Proteins; TurboID; streptavidin imaging; fluorescenční mikroskopie; rekombinantní fúzní proteiny; cell biology; protozoální proteiny; streptavidin; Streptavidin; protilátky; Recombinant Fusion Proteins; phase separation; Microscopy, Fluorescence; lidé; Biotinylation